Smart communities in Japan: Requirements and simulation for determining index values - Hiromi Okubo; Yoshiyuki Shimoda; Yuki Kitagawa; Monica Irisa Clara Gondokusuma; Ayumu Sawamura; Katsuhisa Deto (Journal of Urban Management, 2022)
Recently, smart communities are heeded to in Japan as a solution to community issues. To properly evaluate the underlying concept, it is necessary to analyze smart cities in terms of local energy and environmental aspects, as well as disaster resilience. This research aimed to summarize the requirements for Japanese smart communities, and provide this information to municipalities, city planners, and regional developers in warmer climates, or countries where few precedents exist. Nine cases were reviewed in Japan, and four in Europe and the US to organize smart community requirements into three areas: environment, social, and safety-security. Additionally, bottom-up simulations were used to quantitatively evaluate the effects of energy technology introduction, emergency Life Continuity Plans (LCPs), and changes in energy performance owing to household compositional differences. The results showed that a typical Japanese smart community (containing Fuel cell, PV, and battery) has the capacity to become a positive energy district, generating 1916~​GJ~​yr−1, and maintain power throughout a one-week power outage if shared within the community (save for the highest temperature week in August). Conversely, Japanese smart communities lacked consideration of residential diversity and creative landscapes.
Keywords: 710